Contextualization of Wasathiyah Values in Haji Sulong's thoughts for Islamic Education Renewal in South Thailand - Sri Sumarni (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
Since Pattani region entered into a nation state of Thailand there have been various policies of assimilation toward the people of Southern Thailand. Until the present time, this policy has caused a conflict to both sides. The main problem is not about religious issues, but the ethnicity to maintain Malay-Muslim identity from Thai-Buddhist threats. Efforts to understand each other's identity, both Malay-Islamic and Thai-Buddhist can be continuously explored, such as: Islamic values ​​as ummatan wasathan and Buddha's Majjhima-patipada oriented to the idea of ​​"middle way". Efforts to understand each other can be done through education starting from Early Childhood Education to Higher Education. Efforts to understand both identities can also be done by a figure, such as Haji Sulong. Haji Sulong's struggle was initially prioritized the renewal of the Islamic Education System in Pattani, both the management and the curriculum. But along with the royal policy that continues to pressure the people of Southern Thailand, Haji Sulong also plunged into the political world. Haji Sulong heroic values ​​can be a transformative spirit for the people of South Thailand, such as: (1) Innovative value, (2) Caring values, (3) Values ​​of love/empathy, (4) Prudence, (5) The value of self-control, (6) The value of justice, (7) The value of courage, and etc.